Seismic Performance Evaluation of RCC Hospital Buildings in Pokhara (OODBODHAN, 2026)
Hospitals are the critical infrastructures that must remain operational during and after the seismic events. Pokhara is located in the high seismic zone and faces significant earthquake risk, which impose threat to safety and strength of the hospital buildings. Despite their importance, existing research lacks the study on seismic performance with special focus on Reinforced Cement Concrete (RCC) hospital buildings in Pokhara. This study addresses this gap by evaluating the Seismic Performance of RCC Hospital buildings using Incremental Dynamic Analysis (IDA) and Fragility Analysis. Two RCC framed structures, Block A (without shear wall) and Block B (with shear wall at lift core) were modelled in ETABS V21 and subjected to six representative ground motions to perform Non-Linear Time History Analysis (NLTHA). Seismic Performance were evaluated in-terms of Inter-Story Drift Ratio (IDR), with Peak Ground Acceleration (PGA) serving as Intensity Measure (IM). Finally, IDA curves were generated and fragility curves were developed based on HAZUS-defined drift limits for four damage states. Results indicate that Block A exhibited higher IDR demands (upto 5.7%) compared to Block B (upto 3.27%) for PGA upto 2g. For 0.35g PGA, Block A showed IDR of 1.4% while Block B demonstrated IDR of 0.57%. Fragility analysis revealed Block A had less than 0.3% probability of collapse, while Block B demonstrated resilience by reaching only lower damage states at 0.35g. For 0.35g PGA, Block A displayed 99% and 9% probability of exceeding Moderate and Extensive Damage State respectively. Similarly, for Block B at 0.35g, there is 99% and 3% probability of exceeding Slight and Moderate Damage State respectively. IDA and Fragility analysis of the building showed that the building remains in an operational state after Maximum Considered Earthquake level ground motions, requiring only minor non-structural repairs.